Sensitivity Analysis of Multiobjective Optimization Problems with Parameterized Quasi-Variational Inequalities. (25th January 2018) - Pang, Li-Ping; Meng, Fan-Yun; Lv, Jian; Tian, Qi
ABSTRACT: This paper mainly establishes the sensitivity analysis of a multiobjective optimization problem with parameterized quasi-variational inequalities (QVIs). Using the (regular) coderivative of the associated epigraphical multifunction, the (regular) subdifferentials of the efficient frontier maps are estimated, which involve the (regular) coderivatives of the solution mapping to the parameterized QVIs. Under the linear independent constraint qualification, the defined auxiliary set-valued mappings in the parameterized QVIs are clam. The detailed formulae of subdifferentials of the efficient frontier maps are obtained and examples are simultaneously provided for analyzing and illustrating the obtained results.